2019
DOI: 10.1093/jmammal/gyz196
|View full text |Cite
|
Sign up to set email alerts
|

A precarious future for distinctive peripheral populations of meadow voles (Microtus pennsylvanicus)

Abstract: Conservation efforts rely on robust taxonomic assessments that should be based on critical assessment of interspecific boundaries, infraspecific variation, and potentially distinctive peripheral populations. The meadow vole (Microtus pennsylvanicus) is widely distributed across North America, including 28 morphologically defined subspecies and numerous isolated populations. Because some subspecies are of high conservation concern, we examined geographic variation across the range of the species to test existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 88 publications
0
23
0
Order By: Relevance
“…The genus Microtus consists of 62 species of voles distributed throughout North America, Europe, and Asia [1]. Microtus is believed to have experienced rapid speciation and diversification, with all speciation events occurring within the past four million years [2, 3], and it has been suggested that some nominal species, such as M. pennsylvanicus , contain cryptic diversity [4]. Microtus has been an important model system across multiple biological disciplines, including studies of adaptation (e.g., [5]), infectious disease (e.g., [6]), parental care (e.g., [7]), and population dynamics (reviewed in [8]).…”
Section: Contextmentioning
confidence: 99%
“…The genus Microtus consists of 62 species of voles distributed throughout North America, Europe, and Asia [1]. Microtus is believed to have experienced rapid speciation and diversification, with all speciation events occurring within the past four million years [2, 3], and it has been suggested that some nominal species, such as M. pennsylvanicus , contain cryptic diversity [4]. Microtus has been an important model system across multiple biological disciplines, including studies of adaptation (e.g., [5]), infectious disease (e.g., [6]), parental care (e.g., [7]), and population dynamics (reviewed in [8]).…”
Section: Contextmentioning
confidence: 99%
“…1). In the Atlantic region, we compared 11 island and mainland populations ranging 8.0 degrees latitude (38°05'24''–46°05'24''N), which fall into the eastern mitochondrial clade identified by Jackson and Cook (2020). In this sample, the island populations form two clusters: Fox and Islesboro Islands in the north off the coast of Maine, and Nantucket, Long Island and others clustering around the coasts of New York and Cape Cod to the south.…”
Section: Methodsmentioning
confidence: 99%
“…In this system, islands were connected to the mainland during the last glacial maximum (LGM), providing opportunity for potential widespread dispersal (Weddle and Choate 1983, Darvill et al 2018). So, current island occupants were likely marooned with rising sea levels rather than colonized islands via over‐water dispersal (Weddle and Choate 1983, Jackson and Cook 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such shifts have already been observed within the range of voles, and are likely to continue if winters become increasingly mild (Osland et al, 2013(Osland et al, , 2020Stevens et al, 2006). Thus, despite the persistence of voles since the Pleistocene, novel climate-mediated factors may threaten this climate relict (Hotaling et al, 2010;Jackson & Cook, 2020).…”
mentioning
confidence: 91%
“…The Florida saltmarsh vole (Microtus pennsylvanicus dukecampbelli; hereafter: "vole") is a climate relict from the Pleistocene epoch when the global climate was cooler (Woods et al, 1982). Though previously considered a subpopulation of the more widespread meadow vole (Microtus pennsylvanicus), more recent genetic analysis indicated that the population likely represents a distinct species (Jackson & Cook, 2020). Meadow voles appear to have been more widespread in Florida during the Pleistocene, but their southern range limit contracted poleward as the climate warmed during the Holocene (Jackson & Cook, 2020;Martin, 1968;Woods et al, 1982).…”
mentioning
confidence: 99%